Knowledge or content? The philosophical boundaries in e-learning pedagogical theories. - Silva, Nuno (2014)
The evolution of educational technologies engages dissimilar pedagogical strategies; however, the existent work in e-learning seems to neglect hitherto an important discussion: what is knowledge, and what is content in the different pedagogical approaches? To promote such discussion e-learning definition and featured technologies will be under debate given their influence over the pedagogical choice. Afterwards, the attempt is to define knowledge and content, as well as to present their possible boundaries. Finally, we approach pedagogy and its theories to frame what is knowledge or content in each of those theories.